The Mycoplasma spp. ‘Releasome’: A New Concept for a Long-Known Phenomenon - Gaurivaud, Patrice; Tardy, Florence (Frontiers in Microbiology, 2022)
The bacterial secretome comprises polypeptides expressed at the cell surface or released into the extracellular environment as well as the corresponding secretion machineries. Despite their reduced coding capacities, Mycoplasma spp. are able to produce and release several components into their environment, including polypeptides, exopolysaccharides and extracellular vesicles. Technical difficulties in purifying these elements from the complex broth media used to grow mycoplasmas have recently been overcome by optimizing growth conditions and switching to chemically defined culture media. However, the secretion pathways responsible for the release of these structurally varied elements are still poorly described in mycoplasmas. We propose the use of the term ‘releasome,’ instead of secretome, to refer to molecules released by mycoplasmas into their environment. The aim of this review is to more precisely delineate the elements that should be considered part of the mycoplasmal releasome and their role in the interplay of mycoplasmas with host cells and tissues.